Rancang bangun sistem sensor nirkabel untuk memantau kecepatan dan arah aliran - Erryk Yustisianto Putro; Suryono Suryono (Youngster Physics Journal, 2017)
On research wirelees sensor system design for monitoring velocity and direction of water. Monitoring the flow of water is needed in the field of irrigation and industry, mitigation of floods and many other applications. The system is made comprises a remote terminal unit (RTU) and control terminal unit (CTU). On the RTU are ATSAM3X8E microcontroller and microprocessor that transmit data through WiFi and received by personal computers that are in the CTU. RTU transmit the bases data to the CTU. The water velocity outtakes using waterflow sensor, which changes the magnitude of the flow rate to a variable frequency. Sensor waterflow associated with Schmitt trigger so that the output signal of the sensor is more accurate when read by the microcontroller. The frequency is read by the microcontroller and sent to a RTU computer. Flow direction in the sensor using a potensio that changed the angle (direction) into the barriers and voltage. The data is read by the analog to digital converter (ADC) microcontroller and sent to a RTU computer. Data flow velocities is calibrated with a standard velocitiy and linear correlation coefficient of 0.9997. Results of testing the angle of the magnitude of standard (protractor) linear correlation coefficient  of 1. From these tests it can be concluded that the equipment is fit for use. Keywords : monitoring system, microcontroller, RTU ,CTU, waterflow sensor